Mesenchymal stem cell expression of SDF‐1β synergizes with BMP‐2 to augment cell‐mediated healing of critical‐sized mouse calvarial defects. (31st July 2015) - Herberg, Samuel; Aguilar‐Perez, Alexandra; Howie, R. Nicole; Kondrikova, Galina; Periyasamy‐Thandavan, Sudharsan; Elsalanty, Mohammed E.; Shi, Xingming; Hill, William D.; Cray, James J.
Abstract: Bone has the potential for spontaneous healing. This process, however, often fails in patients with comorbidities. Tissue engineering combining functional cells, biomaterials and osteoinductive cues may provide alternative treatment strategies. We have recently demonstrated that stromal cell‐derived factor‐1 β (SDF‐1 β ) works in concert with bone morphogenetic protein‐2 (BMP‐2) to potentiate osteogenic differentiation of bone marrow‐derived mesenchymal stem/stromal cells (BMSCs). Here, we test the hypothesis that SDF‐1 β overexpressed in Tet‐Off‐SDF‐1 β BMSCs, delivered on acellular dermal matrix (ADM), synergistically augments BMP‐2‐induced healing of critical‐sized mouse calvarial defects. BMSC therapies alone showed limited bone healing, which was increased with co‐delivery of BMP‐2. This was further enhanced in Tet‐Off‐SDF‐1 β BMSCs + BMP‐2. Only limited BMSC retention on ADM constructs was observed after 4 weeks in vivo, which was increased with BMP‐2 co‐delivery. In vitro cell proliferation studies showed that supplementing BMP‐2 to Tet‐Off BMSCs significantly increased the cell number during the first 24 h. Consequently, the increased cell numbers decreased the detectable BMP‐2 levels in the medium, but increased cell‐associated BMP‐2. The data suggest that SDF‐1 β provides synergistic effects supporting BMP‐2‐induced, BMSC‐mediated bone formation and appears suitable for optimization of bone augmentation in combination therapy protocols. Copyright © 2015 John Wiley & Sons, Ltd.